Best Practice Guidance for Effective Methane Drainage and Use in Coal Mines - United Nations (United Nations, 2010)
Coal mines are not only a safety management challenge but also a major source of greenhouse gas emissions. Methane release during coal mining creates unsafe working conditions in underground coal mines around the world. This Guidance is intended to provide a genuine contribution to improve mine safety practices at active underground coal mines, by supporting safer mining practices to reduce fatalities, injuries, and property losses, while encouraging the use of coal mine methane (CMM) to reduce greenhouse gas emissions and utilize otherwise –wasted energy resources.